Clinical and patient‐reported outcomes of bilateral implantation of a +2.5 diopter multifocal intraocular lens. Issue 3 (January 2017) - Maxwell, Andrew; Holland, Edward; Cibik, Lisa; Fakadej, Anna; Foster, Gary; Grosinger, Les; Moyes, Andrew; Nielsen, Stephen; Silverstein, Steven; Toyos, Melissa; Weinstein, Arthur; Hartzell, Scott
Abstract : Purpose : To assess the effectiveness and safety of a multifocal intraocular lens (IOL) with +2.5 diopter (D) additional power compared with a monofocal IOL. Setting : Fifteen sites in the United States. Design : Prospective randomized patient‐ and observer‐masked clinical trial. Methods : Randomized patients received multifocal or monofocal IOLs bilaterally. Visual acuity (33 cm, 40 cm, 53 cm, 60 cm, 4 m) was measured; safety was assessed through adverse event rates. Patient‐reported visual outcomes were evaluated using the Visual Tasks questionnaire. The frequency and severity of visual disturbances were evaluated using the Assessment of Photic Phenomena and Lens EffectS questionnaire. Results : The multifocal IOL (n = 155) provided better corrected distance visual acuity at 53 cm than the monofocal IOL (n = 165) (0.322 versus 0.512 logMAR; between‐group difference, −0.190 logMAR; P < .0001) and 40 cm but not at 4 m. Ocular adverse event rates were less than 3.84% in both groups. Serious adverse event rates were comparable between the 2 IOL types. Patients with multifocal IOLs reported less difficulty with near tasks (with and without correction) and intermediate tasks (without correction). Difficulty with extended‐intermediate and distance tasks was similar between groups. The most frequently reported self‐rated severe phenomena were halos, starbursts, and glare. Most patients (monofocal ≥72%; multifocal ≥73%) reported never experiencing blurred, distorted, or double vision. Conclusions : The +2.5 D multifocal IOL provided better vision at 40 cm and 53 cm and similar vision at 4 m compared with the monofocal IOL. Safety profiles and visual phenomena were comparable between groups.